“We are in the forgotten corner!” a qualitative study of experiences and challenges among Chinese older women at the onset of acute myocardial infarction - Yu, Huidan; Liu, Huafen; An, Zifen; Zhou, Jiali; Meng, Xianmei; Luo, Xianwu; Zhou, Xiaoyang (Frontiers in Public Health, 2023)
Background Acute myocardial infarction (AMI) is a common and serious cardiovascular disease (CVD) that is one of the leading causes of death among women globally and in China. However, there are sex-associated differences and inequalities in the detection and management of AMI, especially in older people. There is little research demonstrating how challenges and barriers affect older women’s help-seeking behavior and health-related procedures in China. Purpose The objective of this study was to explore the experiences of older women with AMI, focusing on their perception, challenges, and coping strategies at the onset of AMI in Wuhan, China. Methods This study utilized a qualitative research design approach and conducted semi-structured, in-depth, and audio-recorded interviews with 18 women aged 65–84 years, purposively selected from two tertiary hospitals in Wuhan City from November 2021 to April 2022. Results Interpretative Phenomenological Analysis (IPA) was used in this study to analyze the data on 18 participants and three major themes were generated: disease perception disorder, negative coping strategies, and barriers due to social-environmental contexts. Conclusion To reduce older women’s delay in seeking help, healthcare professionals should provide public health education that emphasizes sex-related disparities, and age-specific knowledge-attitude aspects to high-risk groups. Policy-based and health administration recommendations, including e-health information support, access to care, and social-environmental factors, should be highlighted to promote women’s health behavior.